Enhancing the Bioavailability of Poorly Soluble Drugs - Rodolfo Pinal (MDPI AG, 2024)
The poor aqueous solubility of drugs is such a frequent challenge to drug absorption, bioavailability, and drug delivery that it is occasionally spoken about as an "unwritten rule" in drug product development [...]